2016
DOI: 10.1021/acs.nanolett.5b03748
|View full text |Cite
|
Sign up to set email alerts
|

Radial Stark Effect in (In,Ga)N Nanowires

Abstract: We study the luminescence of unintentionally doped and Si-doped InxGa1-xN nanowires with a low In content (x < 0.2) grown by molecular beam epitaxy on Si substrates. The emission band observed at 300 K from the unintentionally doped samples is centered at much lower energies (800 meV) than expected from the In content measured by X-ray diffractometry and energy dispersive X-ray spectroscopy. This discrepancy arises from the pinning of the Fermi level at the sidewalls of the nanowires, which gives rise to stron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 67 publications
4
29
0
Order By: Relevance
“…Therefore, we propose that •ClO n H m and/or •H terminations at the GaN(1 100) and (0001) surfaces act as surface donors. Overall, as shown in Table I, it is clear that the three cleaning steps investigated here can be used to tailor the GaN surface BB over several hundreds of meV, as qualitatively intended in other reports [7,51].…”
Section: B Band Bendingsupporting
confidence: 56%
“…Therefore, we propose that •ClO n H m and/or •H terminations at the GaN(1 100) and (0001) surfaces act as surface donors. Overall, as shown in Table I, it is clear that the three cleaning steps investigated here can be used to tailor the GaN surface BB over several hundreds of meV, as qualitatively intended in other reports [7,51].…”
Section: B Band Bendingsupporting
confidence: 56%
“…With the rapid development of the InGaN alloy based blue-green light emitting diodes, recently, the CL effect induced by structural imperfections has been increasingly addressed 1921 . For example, it has been well shown that localized carriers due to alloy disorder, especially indium content fluctuation, can produce efficient luminescence and unusual thermodynamic behaviors 1928 .…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be moderately mitigated in the NW geometry as a result of lateral strain relief during growth. Several efforts already have been made to understand the QCSE for GaN/InGaN-based LEDs, 96,99,101,[103][104][105][106][107] but there were limited related studies on GaN/AlN or GaN/AlGaN-based UV LEDs. 108,109 In this regards, Leroux et al reported an internal electric field strength of 0.45 MV∕cm in AlGaN/GaN structures by varying the well thickness.…”
Section: Quantum-confined Stark Effect and Strain Issuesmentioning
confidence: 99%
“…The excited carriers may pass through an intermediate energy state induced by the localized defects, 64 and other nonradiative recombination sites, thereby resulting in a reduction in the light-emitter performances. 107 To solve this problem, we have recently demonstrated that the use of long-carbon chained octadecanethiol (ODT) surface treatment of group-III nitride NWs-LED improves the light emission intensity due to a reduction in the SRH recombination and an increase in carrier lifetime. 64 InGaN/GaN NWs were soaked in a mix of ODT, ethanol, and NH 4 OH and kept at 60°C.…”
Section: Doping In Algan Nanowiresmentioning
confidence: 99%